LEARNING STYLES AND VOCABULARY MASTERY OF STUDENTS: A CORRELATIONAL ANALYSIS - Yuliani, Sri; Sulaiman, Masagus; Rizki, Vania Fidela; Hartati, Sri; Septarini, Dian (English Community Journal, 2024)
This study was aimed at determining whether or not there was a significant correlation between learning style and vocabulary mastery of the Eighth Grade Students of SMP Negeri 11 Palembang. This research employed correlational design and 34 students used as the sample of this study. To collect the data, the researchers used tests and questionnaires. To analyze the data, Pearson product moment correlation was applied. The results based on correlation coefficient showed that there was no correlation because the correlation coefficient (r-obtained) of -0.224 was lower than (r-table) 0.334. Yet, the results based on the interpretations of the correlation value showed that there was low correlation because r-obtained was -0.224 within the correlation value of 0.200-0.400. In conclusion, there is correlation between learning styles and vocabulary mastery of the Eighth Grade Students of SMP Negeri 11 Palembang